2012
DOI: 10.1111/j.1365-2966.2012.21141.x
|View full text |Cite
|
Sign up to set email alerts
|

On the density-profile slope of clusters of galaxies

Abstract: The present paper extends a previous study of Del Popolo to clusters of galaxies, considering how baryon–dark matter (DM) interplay shapes the density profiles of dwarf galaxies. Cluster density profiles are determined taking into account dynamical friction, random and ordered angular momentum and the response of DM haloes to condensation of baryons. We find that haloes containing only DM are characterized by Einasto’s profiles, and that profiles flatten with increasing content of baryons and increasing values… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 171 publications
(354 reference statements)
5
54
1
Order By: Relevance
“…6 (the non-extrapolated part of the plot) of [102], in terms of V c (which is 2.8 × 10 − 2M 0.316 vir [111]). We also found that the inner slope depends on the total baryonic content to total mass ratio [27], as seen later in [102]. [20,21] show a comparison of the change of the inner slope with mass with the simulations of [102].…”
Section: Ii3 Star Formation and Feedbacksupporting
confidence: 63%
See 1 more Smart Citation
“…6 (the non-extrapolated part of the plot) of [102], in terms of V c (which is 2.8 × 10 − 2M 0.316 vir [111]). We also found that the inner slope depends on the total baryonic content to total mass ratio [27], as seen later in [102]. [20,21] show a comparison of the change of the inner slope with mass with the simulations of [102].…”
Section: Ii3 Star Formation and Feedbacksupporting
confidence: 63%
“…Here we recall the model used above. First introduced by [17,18], many of its features were developed in [19][20][21], and allowed studies of the density profiles' universality [22,23], of the density profile of galaxies [24][25][26] and clusters [25,27], and of the inner surface-density of galaxies [28].…”
Section: Modelmentioning
confidence: 99%
“…Despite recent progress in complex hydrodynamical simulations of clusters, there is still no consensus on the net effect of such feedback mechanisms on the inner density slope (see, e.g., Gnedin et al 2004;Martizzi et al 2012;Schaller et al 2015). In addition, dynamical processes due to infalling galaxies may also play a relevant role in producing a flat central slope (Nipoti et al 2004;Del Popolo 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this process transfers kinetic energy from baryons to dark matter, and this translates into a flattening of the dark matter density profile (e.g. El-Zant et al 2001;Del Popolo 2012).…”
Section: Stellar Mass Density Profilementioning
confidence: 99%